Protein Tyrosine Kinase 7 Regulates EGFR/Akt Signaling Pathway and Correlates With Malignant Progression in Triple-Negative Breast Cancer - Cui, Nai-Peng; Qiao, Shu; Jiang, Shan; Hu, Jin-Lin; Wang, Ting-Ting; Liu, Wen-Wen; Qin, Yan; Wang, Ya-Nan; Zheng, Li-Shuang; Zhang, Jin-Chao; Ma, Yong-Ping; Chen, Bao-Ping; et al. (Frontiers in Oncology, 2021)
Purpose: Triple-negative breast cancer (TNBC), the most aggressive subtype of breast cancer, is associated with high invasiveness, high metastatic occurrence and poor prognosis. Protein tyrosine kinase 7 (PTK7) plays an important role in multiple cancers. However, the role of PTK7 in TNBC has not been well addressed. This study was performed to evaluate the role of PTK7 in the progression of TNBC. Methods: Correlation of PTK7 expression with clinicopathological parameters was assessed using tissue microarray immunohistochemistry (IHC) staining in 280 patients with breast cancer. PTK7 expression in TNBC (MDA-MB-468, MDA-MB-436 and MDA-MB-231) and non-TNBC (MCF7 and SK-BR-3) breast cancer cell lines were examined using immunoblotting assay. PTK7 correlated genes in invasive breast carcinoma were analyzed using cBioPortal breast cancer datasets including 1,904 patients. PTK7 overexpressed or knockdown TNBC cell lines (MDA-MB-468 and MDA-MB-436) were used to analyze the potential roles of PTK7 in TNBC metastasis and tumor progression. A TNBC tumor bearing mouse model was established to further analyze the role of PTK7 in TNBC tumorigenicity in vivo. Results: PTK7 is highly expressed in breast cancer and correlates with worse prognosis and associates with tumor metastasis and progression in TNBC. Co-expression analysis and gain or loss of function of PTK7 in TNBC cell lines revealed that PTK7 participates in EGFR/Akt signaling regulation and associated with extracellular matrix organization and migration genes in breast cancer, including COL1A1, FN1, WNT5B, MMP11, MMP14 and SDC1. Gain or loss of function experiments of PTK7 suggested that PTK7 promotes proliferation and migration in TNBC cell lines. PTK7 knockdown MDA-MB-468 cell bearing mouse model further demonstrated that PTK7-deficiency inhibits TNBC tumor progression in vivo. Conclusion: This study identified PTK7 as a potential marker of worse prognosis in TNBC and revealed PTK7 promotes TNBC metastasis and progression via EGFR/Akt signaling pathway.